PENGARUH TERAPI TERTAWA TERHADAP STRESS PADA LANSIA HIPERTENSI DI DESA MLANDANGAN KECAMATAN PACE KABUPATEN NGANJUK - Heru Wahyudi; Rahayu Budi Utami; Kharisma Intan Shofiyana (LPPM STIKes SATRIA BHAKTI NGANJUK, 2023)
Stress is the body's reaction to something that causes pressure to change and emotional tension ( Ramdhani, 2013). The elderly are very susceptible to stress disorders becausethere is an aging process where there is a decrease in physical ability. Stress in the elderly oftenoccurs due to factors,body conditions, environmental conditions, external stimuli or events thatthreaten their physical health (Ramdhani, 2013). The purpose of this study was to determine the effectof laughter therapy on stress levels in elderly hypertension in Mlandangan Village, Pace District,Nganjuk Regency. Methods pre-experimental one-group pre-post test design, which carried out on18-27 May 2022 in Mlandangan Village. 70 elderly. Sampling technique. using purposive sampling.The sample is 10 respondents. The independent variable in this study is Laughter Therapy and thedependent variable in this study is the level of stress.